Konstanzer Seminar on Monetary Theory and Monetary Policy - Roland Schmidt (Kredit und Kapital, 1989)
Konstanzer Seminar on Monetary Theory and Monetary Policy Das diesjährige 20. Konstanzer Seminar on Monetary Theory and Monetary Policy beschäftigte sich schwerpunktmäßig mit den Folgen der zunehmenden monetären Integration der Volkswirtschaften. Ein Meinungsaustausch mit Vertretern von Zentralbanken rundete das Programm ab. Der Bericht faßt die Ergebnisse der vorgetragenen Studien und die Diskussionen zusammen – – Konstanzer Seminar on Monetary Theory and Monetary Policy The 20th Konstanz Seminar on Monetary Theory and Monetary Policy dealt with the impacts of the especially in Europe prevailing increase in monetary integration. A panel discussion on monetary cooperation with representatives of several central banks supplemented the program. This report summarizes the papers, and presents the discussions
Keywords: 330